Human-centred design for IT service management - Macdermid, Katrina (TSO, The Stationery Office, 2022)
Humanising IT™ applies human-centred design principles to the world of IT service management. Those who have any role in delivering IT services, from service desk analysts to software developers, CIOs and every human in between, will learn that to improve IT service management, you must prioritise the human experience. Topics to improve your understanding include: • An overview of human-centred design • How IT service management should serve the wider goals of the business • How the DVF (desirability, viability, feasibility) model can be applied • The four main phases of the Double Diamond model • Integrating the five Ps of human-centred design into IT service management. Under the guidance of Katrina Macdermid, an internationally recognised thought leader on IT service management, you are certain to improve your success in the wider business world by learning to put people and the user experience first.
Keywords: tietotekniikka; palvelut; tietotekniikka-ala; asiakaslähtöisyys; käyttäjälähtöisyys; johtaminen; Information technology; Services; User-centered system design; Human-computer interaction